The TRPV6 Calcium Channel and Its Relationship with Cancer - Yifang Wang; Xiaoling Deng; Rui Zhang; Hao Lyu; Shuai Xiao; Dong Guo; Declan William Ali; Marek Michalak; Cefan Zhou; Xing-Zhen Chen; Jingfeng Tang (Biology, 2024)
Transient receptor potential vanilloid-6 (TRPV6) is a cation channel belonging to the TRP superfamily, specifically the vanilloid subfamily, and is the sixth member of this subfamily. Its presence in the body is primarily limited to the skin, ovaries, kidney, testes, and digestive tract epithelium. The body maintains calcium homeostasis using the TRPV6 channel, which has a greater calcium selectivity than the other TRP channels. Several pieces of evidence suggest that it is upregulated in the advanced stages of thyroid, ovarian, breast, colon, and prostate cancers. The function of TRPV6 in regulating calcium signaling in cancer will be covered in this review, along with its potential applications as a cancer treatment target.